Amelioration of gut dysbiosis-induced cognitive deterioration by repeated administration of human clostridium butyricum: targeting intestinal and blood–brain barrier - Dalia Azmy Elberry; Maha Gamal; Zeinab Gawish; Esraa A. Hegazy; Sara Adel Hosny; Laila Ahmed Rashed; Marwa Nagi Mehesen; Asmaa Mohammed ShamsEldeen (Future Journal of Pharmaceutical Sciences)
Abstract Background Disturbed intestinal integrity and increased permeability are linked to dysbiosis. This disruption involves GIT-related and unrelated diseases, such as neurological diseases. Intake of a high-fat diet (HFD) leads to an imbalance of gut microbiota and regression of bacteria producing “short-chain fatty acids (SCFAs)”. These SCFAs can modulate brain functions. Therefore, we investigated the therapeutic effect of Clostridium Butyricum (CB) bacteria extracted from human faeces on intestinal and neurological impairments induced by HFD and explored their modulation of tight junction protein expression. Materials and methods Twenty-four adult male rats were classified into the control group, which received regular rat chow; the HFD group, which received HFD for 16 weeks; and the HFD-Microbiota group, which received HFD as in group II for 16 weeks, but from week 9 received CB (dose of 2 ml (2.3 × 1011 cfu/ml) daily till scarification. Results The microbiota improved working memory, episodic-like memory, and emotional memory. Also, there was a substantial decline in the animals’ body weights, serum lipopolysaccharides, interleukin-1β, tumour necrosis factor-α, insulin, glucose, and HOMA index compared to the HFD group. A remarkable increase in brain and colonic claudin-5 and occluding expression of its gene in the microbiota-treated group in comparison with the HFD group was reported. SCFAs, intestinal, brain claudin-5, and occludin genes were positively correlated. Also, a positive correlation was found between the F/B ratio and both brain beta-amyloid and Tau proteins. Conclusion Repeated intake of CB hindered systemic /neuroinflammation, enhanced the tight junction proteins’ expression in the gut/brain barrier, and improved cognitive functions.